2017
DOI: 10.1080/17470218.2016.1171886
|View full text |Cite
|
Sign up to set email alerts
|

Associative independence revisited: competition between conflicting associations can be resolved or even reversed in one trial

Abstract: In one type of association-memory paradigm, after studying pairs of the form AB, AC, participants must recall both B and C in response to A. Counterintuitively, yet often replicated, recall probabilities of B and C are typically uncorrelated ("associative independence"). This face-value independence is now understood to reflect a negative correlation due to AB and AC competing, approximately offset by a positive correlation produced by subject- and item-variability. The outcome might vary with stimulus materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 64 publications
(116 reference statements)
11
29
0
Order By: Relevance
“…Likewise, Burton et al (2015), employing a similar design, observed a positive correlation between recall of B and D given A as a cue. Postman and Gray (1977) also observed that when given A while having studied A-B, A-D, participants were most successful at retrieving D if they first recalled B.…”
Section: Proactive Interference and Facilitationmentioning
confidence: 85%
See 2 more Smart Citations
“…Likewise, Burton et al (2015), employing a similar design, observed a positive correlation between recall of B and D given A as a cue. Postman and Gray (1977) also observed that when given A while having studied A-B, A-D, participants were most successful at retrieving D if they first recalled B.…”
Section: Proactive Interference and Facilitationmentioning
confidence: 85%
“…The variability in recognizing repeated items across lists may also explain why proactive facilitation has gone largely unnoticed in the literature for so very long. As discussed, Burton et al (2015) have suggested that the differences in paired-associate techniques (e.g., learning to a criterion) may have contributed to masking the proactive facilitation effects.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies reported here, we used events consisting of four pairs. Each pair shared a common component (A-B, B-C, C-D, D-A), to promote retrieval of the previous pair during study (Caplan et al 2014), as well as to allow for components to be integrated into an event (Burton et al 2017;Schlichting and Preston 2017). We extend previous literature on schema effects by actively eliciting contextual predictions that stem from existing schemas, as opposed to relying solely on the level of relatedness of two items.…”
mentioning
confidence: 99%
“…Finally, proactive and retroactive interference were measured as a percentage. Using the cued recall results from List 1 and 2, proactive interference was measured by subtracting the percentage of correctly recalled FG pairs from the percentage of AC pairs (i.e., AC-FG) and RI by subtracting the percentage of correctly recalled DE pairs from the percentage of AB pairs (i.e., AB-DE) [65].…”
mentioning
confidence: 99%